Probleme der Übersetzung direktiver Sprechakte aus dem Deutschen ins Bulgarische (Philology, 2023)
Manuals for technical devices can be found in almost every household. They provide instructions for the assembly, use, maintenance and disposal of technical products and are an essential prerequisite for consumer safety. The aim of this article is to examine the means of expressing instructions in the German language and their translation into Bulgarian. Based on Searle’s theory of speech acts, the methods of expressing directive speech acts in German and Bulgarian are analyzed. Comparative analysis of translations of German imperative infinitive constructions to Bulgarian shows that the imperative mood is the preferred equivalent construction in Bulgarian. Furthermore, the analysis demonstrates possible problematic interpretation of German infinitive constructions as descriptive instead of instructive sentences. Finally, strategies to prevent misinterpretations of imperative infinitive constructions are presented.
Keywords: Speech act; Instructions; Imperative; Infinitive